Facial Palsy as Presenting Feature of Relapsing Polychondritis in Association with Myelodysplastic Syndrome - Rahim, Muhammad Abdur; Dewan, Pratik; Haque, Hasna Fahmima; Sultana, Tanvira Afroze; Ahmed, AKM Shaheen; Uddin, Khwaja Nazim (Journal of Medicine, 2015)
Relapsing polychondritis (RP) is a rare systemic inflammatory disorder having predilection for cartilaginous structures specially ears, nose, joints and respiratory tract. Myelodysplastic syndrome (MDS) is an established association. Here we describe case history of a 60-year-old man who had episodic pain involving left external ear, throat and nose, hearing difficulty and lethargy for six months and right sided facial weakness of recent onset. He was anaemic, his left ear was distorted and there was right facial palsy. Investigations revealed him to be a case of RP in association with MDS. His pain and facial palsy improved with prednisolone. J MEDICINE July 2015; 16 (2) : 124-127